The Relaxation Limits of the Two-Fluid Compressible Euler-Maxwell Equations (Journal of Partial Differential Equations, 2018)
In this paper we consider the relaxation limits of the two-fluid Euler-Maxwell systems with initial layer. We construct an asymptotic expansion with initial layer functions and prove the convergence between the exact solutions and the approximate solutions.
Keywords: Euler-Maxwell equation; relaxation limit; initial layer; asymptotic expansion